2019
DOI: 10.3847/1538-4357/ab1752
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Mass of Differentially Rotating Strange Quark Stars

Abstract: We present the first fully relativistic numerical calculations of differentially rotating Strange Quark Stars models for broad ranges of the maximum density and of the degree of differential rotation. Our simulations are performed with the very accurate and stable multi-domain spectral code FlatStar and use the MIT Bag model for describing strange quark matter. Our calculations based on a thorough exploration of the solution space show that the maximum mass of strange stars depends on both the degree of differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In [73] it was found that the function A −1 crit ( max ) for incompressible EOSs first increases to a maximum and subsequently decreases as the energy density increases. This same feature was observed for strangequark-matter EOSs, which may be suitably approximated as homogeneous bodies [77]. We note that similar features 11 We refer to the increase and subsequent decrease of A −1 crit ( max) at values of max above the phase transition (as shown in Figure 14) as a "bump" feature.…”
Section: Eos Typeâsupporting
confidence: 65%
See 1 more Smart Citation
“…In [73] it was found that the function A −1 crit ( max ) for incompressible EOSs first increases to a maximum and subsequently decreases as the energy density increases. This same feature was observed for strangequark-matter EOSs, which may be suitably approximated as homogeneous bodies [77]. We note that similar features 11 We refer to the increase and subsequent decrease of A −1 crit ( max) at values of max above the phase transition (as shown in Figure 14) as a "bump" feature.…”
Section: Eos Typeâsupporting
confidence: 65%
“…Differential rotation plays an important role in temporarily stabilizing a binary neutron star merger remnant, and likely many merger remnants go trough a hypermassive phase (see, e.g., [60,71,72] for recent reviews on binary neutron star mergers). Differentially rotating stars have been shown to exhibit a rich and interesting solution space (see [73][74][75] for polytropes, [70] for hadronic EOSs, and [76,77] for strange quark stars). For instance, as the degree of differential rotation varies, the topology of the star can change from spheroidal to quasi-toroidal, where the maximum energy density does not occur at the geometric center of the star, but in a ring around the stellar center of mass.…”
Section: Introductionmentioning
confidence: 99%
“…is chosen to construct the solutions, in which A is a parameter that characterizes the degree of differential rotation and a normalized version  = A/r e is also often used where r e is the equatorial coordinate radius of the star (for smaller values of Â, the differential rotation degree is higher). Previous initialdata studies [27,29] show that the properties of differentially rotating QSs for a given value of  is quite different from that of NSs. In particular, continuous transition to toroidal sequences (i.e., type C solution according to the classification of [52]) happens at lower degree of differential rotation (at  ∼ 3 for QSs while at  = 1 for NSs).…”
Section: Numerical Setup a Initial Datamentioning
confidence: 96%
“…This requires the modeling of QSs with the tool of general relativistic hydrodynamics as a first step. Previously, various efforts have been made in the calculation of the quasi-/equilibrium structures of uniformly and differentially rotating QSs in general relativity (GR) [24][25][26][27][28][29] as well as the configuration of BQSs in the last orbits [30]. Despite all these attempts in constructing initial data for QSs, the progress in dynamical evolution of them is quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, one can estimate the total mass of the star by solving the Tolman-Oppenheimer-Volkov (TOV) equations [20] numerically [21,22] by adopting the conjecture, proposed by E. Witten [7]. In several recent works [23,24], the limiting mass for spinning quark star is also studied using the same procedure as used for the case of static quark star. But there is no argument in the literature that favors the existence of limiting mass which, like ordinary compact objects [25], depends dominantly on the fundamental constants.…”
Section: Introductionmentioning
confidence: 99%